Perlindungan Data Konsumen Transaksi Online Melalui Penerapan Advance Data Protection System - Wahyu Beny Mukti Setiyawan; Hafid Zakariya; Delia Wahtikasari (Wajah Hukum, 2020)
The concept of a welfare state is the basis for the position and function of government (bestuurfunctie) in modern countries. The application of the law that is obeyed and followed will lead to law and order which maximize the potential of the community. Furthermore, in accordance with the objectives of the state set out in the fourth paragraph of the opening of the 1945 Constitution of the Republic of Indonesia that one of the objectives of the state is to protect the entire Indonesian nation and to advance the general welfare. By the establishment of the country’s goals in the fourth paragraph of the 1945 Constitution of the Republic of Indonesia, the answer is that in fact Indonesia has tried to create a welfare state. The main key in the welfare state is regarding the guarantee of people’s welfare given by the State. Basically, the regulation concerning the right to privacy of personal data is a manifestation of the recognition and protection of basic human rights. Therefore, the drafting of the Personal Data Protection Bill has a strong philosophical foundation and can be accounted for. Decision of the Constitutional Court Number 006 / PUU-I / 2003 further emphasized that the regulation of Personal Data Protection must be in the form of a law. In the Constitutional Court Decision, among others, it was stated that the provisions concerning human rights must be in the form of laws. As a form of the state present to protect as well as the welfare of its people, the government as the highest authority as well as those who run the government is obliged to carry out efforts that are felt needed. One way that the government can do to answer and minimize the problems faced is by implementing the Advance Data Protection System as a form of protection.